Research Streams in Cluster Upgrading. A Literature Review - Marta Gancarczyk; Joanna Bohatkiewicz (Journal of Entrepreneurship, Management and Innovation)

(untitled)
This paper aims to identify and systemize the research streams in regional cluster upgrading. Cluster upgrading belongs to broader research in the dynamics of industrial agglomerations, currently, the major topic in studies on clusters. Within this literature, the upgrading concept differentiates by the focus on structural change in response to the insertion of regional clusters into global value chains (GVCs). Based on the narrative literature review, we identify and discuss two major research streams and classify them as the positive and the normative. Moreover, we elaborate a framework for studying the antecedents of cluster upgrading to conclude with research questions that may serve further systematic reviews and empirical investigations. This paper provides two contributions to the cluster dynamics literature with a focus on the upgrading of industrial agglomerations. First, it offers a comprehensive approach to the cluster upgrading theory by integrating the fragmented research in this area. Second, it proposes a theoretical framework to set up further research directions.